Zero valent metal loaded silica nanoparticles for the removal of TNT from water - Mangal, Harsha (Water science and technology : a journal of the International Association on Water Pollution Research, 2017)
Silica nanoparticles with a surface area of 673.60 m2/g and particle size of 8-12 nm were prepared using aerogel process (AP) followed by super critical drying. Zero valent Fe, Co, Pt, and bimetallic Fe/Pt and Fe/Co were loaded using an incipient wetness impregnation technique and subsequent reduction. Scanning electron microscopy-energy dispersive X-ray (SEM-EDX) and transmission electron microscopy-energy dispersive X-ray (TEM-EDX) characterizations indicated fine dispersion of iron on AP-SiO2 +Fe system. Prepared nanoparticles were evaluated for the adsorptive removal of 2,4,6-trinitrotoluene (TNT) from water. Surface area normalized rate constant values indicated the adsorptive removal potential of prepared nanoparticles to be: AP-SiO2 + Fe/Co > AP-SiO2 + Fe > CM (commercial) SiO2 + Fe > AP-SiO2 + Co > AP-SiO2 + Fe/Pt > AP-SiO2 + Pt. Lower pH helped in accelerating the reactive removal of TNT on zero valent iron loaded silica. AP-SiO2 + Fe/Co system showed the maximum adsorption potential (74 mg/g) after five cycles